2015
DOI: 10.1038/npp.2015.178
|View full text |Cite
|
Sign up to set email alerts
|

Stress Modulation of Opposing Circuits in the Bed Nucleus of the Stria Terminalis

Abstract: The anterior bed nucleus of the stria terminalis (BNST) has been recognized as a critical structure in regulating trait anxiety, contextual fear memory, and appetitive behavior, and is known to be sensitive to stress manipulations. As one of the most complex structures in the central nervous system, the intrinsic circuitry of the BNST is largely unknown; however, recent technological developments have allowed researchers to begin to untangle the internal connections of the nucleus. This research has revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
192
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(198 citation statements)
references
References 180 publications
(332 reference statements)
6
192
0
Order By: Relevance
“…The extent of strong inhibitory connections is consistent with earlier findings showing that GABAergic neurons make up a predominant portion of the general makeup of adBNST and glutamatergic neurons only account for a minority of the overall population (Daniel and Rainnie 2016;Larriva-Sahd 2006;Nguyen et al 2015). Given that BSNT receives strong extrinsic excitatory inputs from the amygdala and other brain regions (Daniel and Rainnie 2016;Kim et al 2013), strong local inhibitory connections can play an important role in modulation of these extrinsic inputs.Because both the detailed neuronal morphology revealed by biocytin staining and input mapped profiles were available, we explored the spatial relationship between dendritic fields and input profiles by examining their overlays, as illustrated in Fig. 4.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The extent of strong inhibitory connections is consistent with earlier findings showing that GABAergic neurons make up a predominant portion of the general makeup of adBNST and glutamatergic neurons only account for a minority of the overall population (Daniel and Rainnie 2016;Larriva-Sahd 2006;Nguyen et al 2015). Given that BSNT receives strong extrinsic excitatory inputs from the amygdala and other brain regions (Daniel and Rainnie 2016;Kim et al 2013), strong local inhibitory connections can play an important role in modulation of these extrinsic inputs.Because both the detailed neuronal morphology revealed by biocytin staining and input mapped profiles were available, we explored the spatial relationship between dendritic fields and input profiles by examining their overlays, as illustrated in Fig. 4.…”
supporting
confidence: 79%
“…The BNST coordinates neuroendocrine, autonomic and somatomotor responses to anxiety and emotional aspects of stressful events, and it is identified as a key node in neural networks relevant to pathological anxiety and addiction. This area has received increased attention in light of recent physiological and functional studies (Daniel and Rainnie 2016;Deisseroth 2014;Jennings et al 2013;Johansen 2013;Kim et al 2013).…”
Section: In This Study We Have Applied Photostimulation-based Approamentioning
confidence: 99%
See 1 more Smart Citation
“…Rainnie and colleagues provide a thorough review of the electrophysiological underpinnings of the BNST-dependent stress response (Daniel and Rainnie, 2016). This chapter is followed by a review of new findings of BNST function in humans, in particularly how the human BNST modulates anxiety and stress responses using fMRI approaches (Avery et al, 2016).…”
mentioning
confidence: 99%
“…The BNST is an anatomically complex structure with multiple subdivisions ) and is a node for stress information integration (Lebow and Chen 2016). Initial anatomical studies revealed RXFP3 expression in multiple subdivisions of mouse BNST (Smith et al 2010), but a detailed analysis of RXFP3 expression patterns in the BNST would be required to determine the possible role of these receptors in HPA axis regulation, as activation or inhibition of individual subdivisions of the BNST can have opposing effects (see Biag et al 2012;Daniel and Rainnie 2016). Furthermore, high-frequency stimulation of the BNST produced a reduction in subsequently evoked field potentials in PVN, and this reduction was blocked by an NMDA receptor antagonist, suggesting that PVNprojecting glutamatergic neurons can mediate neuroplasticity within the PVN (Tartar et al 2006).…”
Section: Rxfp3 Expression By Glutamatergic Pvn Afferentsmentioning
confidence: 98%